2018
DOI: 10.1055/a-0592-7512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Moderate Exercise on Post-concussive Symptoms and Cognitive Function after Concussion in Children and Adolescents Compared to Healthy Controls

Abstract: Resolution of post-concussive symptoms (PCS) is a marker of recovery. However, it is unclear whether subtle impairments re-emerge in the context of increased demands. This study examined the effect of strenuous exercise on clinical symptoms and cognitive efficiency in children and adolescents after PCS resolution following concussion. We recruited concussed children and adolescents (n=30) on presentation to an Emergency Department (ED), and compared them to community-sourced non-injured controls (n=30), matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…29,30,33 Additionally, an emerging literature suggests that guided physical activity can be an effective intervention in the post-acute and chronic phases of recovery. 34,35 Results from the DVBIC PRA study provided additional support for these findings, as SMs who engaged in higher levels of physical or vestibular activity during the sub-acute stage (1 month post-injury) reported lower levels of symptoms in the chronic stage (3 months post-injury). 36 This apparent reversal in the effects of activity over time highlights the importance of matching concussion patients' activity levels to their stage of recovery, with a graded increase in activity level as symptoms subside.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 87%
“…29,30,33 Additionally, an emerging literature suggests that guided physical activity can be an effective intervention in the post-acute and chronic phases of recovery. 34,35 Results from the DVBIC PRA study provided additional support for these findings, as SMs who engaged in higher levels of physical or vestibular activity during the sub-acute stage (1 month post-injury) reported lower levels of symptoms in the chronic stage (3 months post-injury). 36 This apparent reversal in the effects of activity over time highlights the importance of matching concussion patients' activity levels to their stage of recovery, with a graded increase in activity level as symptoms subside.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 87%
“…A single blind case series of 11 male retired NFL/CFL players diagnosed with PCS concluded that after ten sessions of specific craniosacral therapy, visceral manipulation, and neural manipulation (CST/VM/NM) therapy resulted in statistically greater improvements in perceived pain intensity, range of motion, memory, cognition, and duration of sleep [19]. Given the statistically significa t improvements seen in this study and the low risk associated with this intervention craniosacral therapy and visceral manipulation may be promising treatment options.…”
Section: Craniosacral Therapy and Visceral Manipulationmentioning
confidence: 99%
“…A review of observational and experimental data presented evidence for subthreshold aerobic exercise as a tool to safely evaluate concussion and speed recovery for patients with PCS [20]. Additionally, the article states that there is emerging evidence for the effectiveness of controlled aerobic exercise in the acute phase after adolescent sports-related concussion.…”
Section: Exercise Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Anderson et al reported reduction of post-concussive symptoms and faster reaction times on computer-based cognitive tasks in children and adolescents with recent concussion after moderate exercise. 8 Identification of PA as an important factor in relation to fatigue after mTBI is a first step to place PA also in the correct perspective in relationship to prevention and rehabilitation of long term post-concussive symptoms.…”
mentioning
confidence: 99%